Characterization of Membrane-Associated Progesterone Receptor Component-2 (MAPRC2) from Trichinella spiralis and Its Interaction with Progesterone and Mifepristone - Muhammad Tahir Aleem; Jiawen Shi; Zhengqing Yu; Zhaohai Wen; Yang Zhang; Meng Liang; Shakeel Ahmed Lakho; Muhammad Haseeb; Haider Ali; Muhammad Waqas Hassan; Xiaokai Song; Xiangrui Li; et al. (Vaccines, 2021)
Trichinellosis is a foodborne zoonotic disease caused by Trichinella spp., including Trichinella spiralis. In the present study, T. spiralis membrane-associated progesterone receptor component-2 (Ts-MAPRC2) gene was cloned and characterized using protein sequencing analysis. Furthermore, the expression, purification, immunoblot assay, binding ability with progesterone antibody, and immunofluorescence assay were performed. A direct effect of progesterone (P4) and mifepristone (RU486) on the Ts-MAPRC2 gene was determined using in vitro cell culture that showed different expression levels at all developmental stages (muscle larvae (ML), female adult worm (F-AL), male adult worm (M-AL), and newborn larvae (NBL)). Subsequently, the in vitro phenotypic effects of P4, RU486, and rTs-MAPRC2-Ab on F-AL and ML stages were measured. Later, the in vivo phenotypic effect and relative mRNA expression of mifepristone on the F-AL stage were studied. Our results revealed that the Ts-MAPRC2 gene is critical to maintaining pregnancy in the female adult worm (F-AL) of T. spiralis. The 300 ng/mL of P4 and 100 ng/mL of RU486 showed downregulation of the Ts-MAPRC2 gene in F-AL (p ≤ 0.05). This plays an important role in abortion and possibly decreases the worm burden of T. spiralis in the host. Only 30 ng/mL P4 showed significant upregulation in F-AL (p ≤ 0.05). The current study provides new insights regarding the antihormone (P4 and RU486) drug design and vaccine therapy of recombinant (rTs-MAPRC2) protein as well as their combined effects to control T. spiralis infection.